Peran Moderasi Corporate Social Responsibility Pada Return on Equity dan Net Profit Margin Terhadap Harga Saham - Handini Ayu Absari; Hayu Wikan Kinasih (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2021)
This study aims to determine whether there is an effect of Return On Equity (ROE) and Net Profit Margin (NPM) on stock prices, moderated by the Corporate Social Responsibility (CSR). The object of this study are companies listed on the Indonesia Stock Exchange (IDX) that use the GRI index over the period 2017 to 2019 to disclose their sustainability reports. By using purposive sampling, this study obtained 34 companies as sample, with the number of observation as much as 102 data. Data were analyzed using moderated regression analysis. The results of this study prove that ROE and NPM has a significant effect on stock prices and CSR proven in moderating the relationship between ROE and NPM on stock prices.